Ownership structures, company size and age, and sustainable development goals are disclosed in the annual report: Is it acceptable to investors? (Survey among publicly listed companies in Indonesia) - Pratama, Arie; Yadiati, Winwin; Jaenudin, Edi (International Journal of Innovative Research and Scientific Studies, 2024)
The point of this study is to look into how much information about the Sustainable Development Goals (SDGs) that shows how companies support global goals is included in their annual reports. It will also look into whether the type of company and its ownership structure affect how much information about the SDGs is included in financial reports. This study also tested whether SDG disclosures influence firm value. Analyzing companies listed on Indonesian stock exchanges will be the method of conducting this research. This study uses secondary data in the form of disclosure information from annual company reports. The data will be further analyzed using content analysis with a matrix referring to SDG reporting in annual reports. The data were described using descriptive statistics and analyzed using Structural Equation Modelling (SEM) and Path analysis. This research showed that company size and company age positively influence SDG disclosure. The higher the ownership concentration in the company, the better the SDG disclosure, and the SDG disclosure positively influences firm value. This research showed that the level of Sustainable Development Goals (SDGs) disclosure among Indonesian companies is currently limited. This research also discovered that companies with greater complexity tend to provide more comprehensive information about their SDG efforts. It is important to focus on improving SDG disclosure among newer companies with lower ownership concentrations. Lastly, this research also indicates a connection between SDG reporting and company value, but the impact of this connection is relatively minor.